DAMPAK SUBSIDI HARGA PUPUK, PDB TIONGKOK DAN KURS TERHADAP NERACA PERDAGANGAN PROVINSI RIAU TAHUN 2000- 2018 - Gustina, Gustina; Rosyetti, Rosyetti; Darmayuda, Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the impact of fertilizer price subsidies, Chinese GDP and the exchange rate on the trade balance of Riau Province in 2000 - 2018. This study uses secondary data obtained from data from the Central Statistics Agency (BPS) and Bank Indonesia. The analytical method used is Multiple Linear Regression Analysis with the technique of least simple squares (Ordinary Least Square (OLS)). Testing is carried out on the hypothesis and the feasibility of data (classical assumptions) using a 5% significance level. Based on the results of the study note that subsidies on fertilizer prices, Chinese GDP and the exchange rate together (simultaneously) significantly influence the trade balance of Riau Province in 2000 - 2018. This can be seen from the significant value of 0.000000, meaning fertilizer price subsidies, GDP China and the exchange rate simultaneously have a significant effect on the trade balance in Riau Province. The magnitude of the effect of fertilizer price subsidies, China's GDP and the exchange rate on the trade balance of Riau province was 88.0991%. Whereas 11,9009% is explained by other variables outside the regression equation. And Partially, subsidies, China's GDP and exchange rates respectively affect the trade balance of Riau Province.Keywords: Subsidies, Chinese GDP, Exchange Rate and Trade Balance